Bimekizumab for the treatment of moderate‐to‐severe plaque psoriasis: efficacy, safety, pharmacokinetics, pharmacodynamics and transcriptomics from a phase IIa, randomized, double‐blind multicentre study. (27th December 2021) - Oliver, R.; Krueger, J.G.; Glatt, S.; Vajjah, P.; Mistry, C.; Page, M.; Edwards, H.; Garcet, S.; Li, X.; Dizier, B.; Maroof, A.; Watling, M.; et al.
Summary: Background: Bimekizumab is a monoclonal antibody that selectively inhibits both interleukin (IL)‐17A and IL‐17F, which is currently under investigation for treatment of moderate‐to‐severe plaque psoriasis. Maintenance dosing every 4 weeks is well established with IL‐17 inhibitors for psoriasis. Objectives: To investigate the possible dosing interval during bimekizumab maintenance therapy to maintain clear skin, to inform phase III studies. Methods: Forty‐nine patients with moderate‐to‐severe plaque psoriasis received bimekizumab 320 mg at weeks 0/4, followed at week 16 by bimekizumab 320 mg ( n = 17) or placebo ( n = 32). Efficacy, safety, pharmacokinetics, immunogenicity and biopsy transcriptomic analyses were assessed to week 28. Results: At week 8, 47% of patients achieved a 100% improvement from baseline in Psoriasis Area and Severity Index (PASI 100), increasing to 57% at week 12 (8 weeks after the second dose) before decreasing. In those who received bimekizumab at week 16, PASI 100 rate increased to comparable peak levels at week 20, but reduced by week 28 to 41% (12 weeks after the third dose). The week 8 transcriptional signature observed in lesional psoriatic skin rapidly normalized to levels consistent with nonlesional skin, resulting in molecular remission. Keratinocyte‐related gene products such as CXCL1 (C‐X‐C motif chemokine ligand 1), IL‐8 (encoded by the CXCL8 gene), CCL20 (C‐C motif chemokine 20), IL‐36γ and IL‐17C were profoundly normalized to levels associated with nonlesional skin. Conclusions: Here, inhibition of IL‐17F in addition to IL‐17A resulted in rapid, deep clinical responses. Additionally, profound normalization of keratinocyte biology and the psoriatic transcriptome was observed, including normalization of both IL17 and IL23 gene expression by week 8. These data provide evidence to support evaluation of bimekizumab maintenance dosing both every 8 and every 4 weeks in phase III clinical trials. Abstract : What is already known about this topic? Strong clinical responses have been demonstrated with biologics that inhibit interleukin (IL)‐17A, and inhibition of this cytokine has been shown to affect the transcriptome of patients with psoriasis. Prolonged maintenance dosing intervals are preferred by patients, with sustainable clinical responses key to improvements in quality of life. Maintenance dosing every 4 weeks is well established with IL‐17A inhibitors in psoriasis. What does this study add? A first assessment of the effects of a monoclonal antibody that selectively inhibits both IL‐17A and IL‐17F on the transcriptome of patients with moderate‐to‐severe plaque psoriasis shows rapid normalization of the transcriptional signature in lesional psoriatic skin after 8 weeks. These data provide evidence to support further evaluation of bimekizumab maintenance dosing both every 8 weeks and every 4 weeks in psoriasis in phase III studies. Linked Comment: S. Gerdes and J. Albrecht. Br J Dermatol 2022; 186 :603–604. Plain language summary available online